Multicentre study of the burden of multidrug-resistant bacteria in the aetiology of infected diabetic foot ulcers - Adeyemi T. Adeyemo; Babatope Kolawole; Vincent O. Rotimi; Aaron O. Aboderin (AOSIS, 2021)
Background: Infected diabetic foot ulcer (IDFU) is a public health issue and the leading cause of non-traumatic limb amputation. Very few published data on IDFU exist in most West African countries. Objective: The study investigated the aetiology and antibacterial drug resistance burden of IDFU in tertiary hospitals in Osun state, Nigeria, between July 2016 and April 2017. Methods: Isolates were cultured from tissue biopsies or aspirates collected from patients with IDFU. Bacterial identification, antibiotic susceptibility testing and phenotypic detection of extended-spectrum beta-lactamase and carbapenemase production were done by established protocols. Specific resistance genes were detected by polymerase chain reaction. Results: There were 218 microorganisms isolated from 93 IDFUs, comprising 129 (59.2%) Gram-negative bacilli (GNB), 59 (27.1%) Gram-positive cocci and 29 (13.3%) anaerobic bacteria. The top five facultative anaerobic bacteria isolated were: Staphylococcus aureus (34; 15.6%), Escherichia coli (23; 10.6%), Pseudomonas aeruginosa (20; 9.2%), Klebsiella pneumoniae (19; 8.7%) and Citrobacter spp. (19; 8.7%). The most common anaerobes were Bacteroides spp. (7; 3.2%) and Peptostreptococcus anaerobius (6; 2.8%). Seventy-four IDFUs (80%) were infected by multidrug-resistant bacteria, predominantly methicillin-resistant S. aureus and GNB producing extended-spectrum β-lactamases, mainly of the CTX-M variety. Only 4 (3.1%) GNB produced carbapenemases encoded predominantly by blaVIM. Factors associated with presence of multidrug-resistant bacteria were peripheral neuropathy (adjusted odds ratio [AOR] = 4.05, p = 0.04) and duration of foot infection of more than 1 month (AOR = 7.63, p = 0.02). Conclusion: Multidrug-resistant facultative anaerobic bacteria are overrepresented as agents of IDFU. A relatively low proportion of the aetiological agents were anaerobic bacteria.